Somatosensory evoked potentials in clinical practice: a review - Fustes, Otto Jesus Hernández; Kay, Cláudia Suemi Kamoi; Lorenzoni, Paulo José; Ducci, Renata Dal-Prá; Werneck, Lineu Cesar; Scola, Rosana Herminia (Arquivos de Neuro-Psiquiatria, 2021)
The authors present a review of the current use of somatosensory evoked potentials (SSEPs) in neurological practice as a non-invasive neurophysiological technique. For this purpose we have reviewed articles published in English or Portuguese in the PubMed and LILACS databases. In this review, we address the role of SSEPs in neurological diseases that affect the central nervous system and the peripheral nervous system, especially in demyelinating diseases, for monitoring coma, trauma and the functioning of sensory pathways during surgical procedures. The latter, along with new areas of research, has become one of the most important applications of SSEPs.
Keywords: Evoked Potentials, Somatosensory; Neurology; Multiple Sclerosis; Coma; Intraoperative Neurophysiological Monitoring